Vertical differential grout pump experimental studies methods validation - Nadobko, Vitalii (Academic journal Industrial Machine Building Civil Engineering, 2019)
The article is devoted to creation and substantiation of experimental research method of vertical differential grout pump with flowing piston mark РН 2-4, developed by researchers at Poltava National Technical Yuri Kondratyuk University. Experiments type has been substantiated, variation intervals of the studied parameters values have been determined, the preparation of the experimental sample of the grout pump for research has been described, an experimental installation for research has been designed, the measuring means have been selected, the conditions for performing the experiments have been determined. This technique enables to find the rational values for the following parameters of the solution pump when working with plaster solutions of different displacement: working body frequency movement, diameter, mass and height of lifting over the valve, the hole diameter in the valve sockets.